GOOD GOVERNANCE DAN TRANSPARANSI RENCANA STRATEGI TERWUJUDNYA AKUNTABILITAS KINERJA PEMERINTAH - Elvia Puspa Dewi (JURNAL LENTERA BISNIS, 2018)
Abstract The implementation of good and clean Government to realize people's aspirations and trusted by the community. the accountability of government agencies is a manifestation of the Government's obligation to account for the implementation of the Government's strategic plan to achieve the goals and objectives. Accountability and transparency of the Government is a prerequisite for the creation of bureaucracy and Government responsive to the will of the people. the importance of accountability and transparency in order to ensure the limited use of resources for various public services that can provide maximum benefit to the community in an efficient, effective, and measurable way. The success of accountability can be achieved by the presence of responsive and accountable leaders to be transparent to the community and their subordinates, in addition to the performance evaluation standards should be disclosed clearly and clearly so that it can be clearly known things that must be accountable.Keywords : Good governance, Trasnparency Strategic Plan, Performance Accountability of Government Agencies.